Clinical implications of a gain-of-function genetic polymorphism in DPYD (rs4294451) in colorectal cancer patients treated with fluoropyrimidines - De Mattia, Elena; Polesel, Jerry; Scarabel, Lucia; Cecchin, Erika (Frontiers in Pharmacology, 2024)
Dihydropyrimidine dehydrogenase (DPD, DPYD) is the rate-limi ng enzyme for the detoxifica on of fluoropyrimidines (FLs). The rs4294451 is a regulatory DPYD polymorphism that has recently been func onally characterized and associated with increased DPD expression in the liver. The aim of the present study was to test the clinical implica ons of being a carrier of rs4294451 in a cohort of 645 FL-treated colorectal cancer pa ents. Carriers of at least one DPYD rs4294451-T variant allele had a lower risk of developing NCI-CTC grade 4-5 hematological (OR=0.39, 95%CI: 0.15-0.98, addi ve model) and hematological/non-hematological (OR=0.44, 95%CI: 0.22-0.88, dominant model) FL-related toxicity. Pa ents with the DPYD rs4294451-T allele also had a longer me to severe toxicity development a er FL treatment start (hematological, HR=0.27, 95%CI: 0.09-0.79, Fine-Gray test= 0.1569; hematological/non-hematological: HR=0.38, 95%CI: 0.17-0.85, Fine-Gray test= 0.0444). It is worth no ng that while being at lower risk of toxicity, DPYD rs4294451-T allele carriers tend also to present a shorter overall survival (HR=1.41, 95%CI:1.05-1.90, log-rank p=0.0406). These findings demonstrate a clinical effect of DPYD-rs4294451 polymorphism coherent with the recently described func onal effect. Further inves ga on is warranted to elucidate the poten al clinical value to the rs4294451 polymorphism as a toxicity and especially as an efficacy marker in colorectal cancer.